Alzheimer's biomarkers in daily practice (ABIDE) project: Rationale and design - de Wilde, Arno; van Maurik, Ingrid S; Kunneman, Marleen; Bouwman, Femke; Zwan, Marissa; Willemse, Eline A.J; Biessels, Geert Jan; Minkman, Mirella; Pel, Ruth; Schoonenboom, Niki S.M; Smets, Ellen M.A; Wattjes, Mike P; et al. (Alzheimer's & dementia : diagnosis, assessment & disease monitoring, 2017)
Abstract Introduction The Alzheimer's biomarkers in daily practice (ABIDE) project is designed to translate knowledge on diagnostic tests (magnetic resonance imaging [MRI], cerebrospinal fluid [CSF], and amyloid positron emission tomography [PET]) to daily clinical practice with a focus on mild cognitive impairment (MCI) Methods ABIDE is a 3-year project with a multifaceted design and is structured into interconnected substudies using both quantitative and qualitative research methods. Results Based on retrospective data, we develop personalized risk estimates for MCI patients. Prospectively, we collect MRI and CSF data from 200 patients from local memory clinics and amyloid PET from 500 patients in a tertiary setting, to optimize application of these tests in daily practice. Furthermore, ABIDE will develop strategies for optimal patient-clinician conversations. Discussion Ultimately, this will result in a set of practical tools for clinicians to support the choice of diagnostic tests and facilitate the interpretation and communication of their results.